Simulations of the dynamics of magnetized jets and cosmic rays in galaxy clusters - Ehlert, Kristian; Pakmor, Rüdiger; Springel, Volker; Pfrommer, Christoph (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Feedback processes by active galactic nuclei in the centres of galaxy clusters appear to prevent large-scale cooling flows and impede star formation.